TEACHER APPROACHES TO TEACHING A LARGE EFL CLASS - Tono Suwartono; Zulia Karini; Oom Diana Pungki (Khazanah Pendidikan, 2019)
This research was aimed to identify problems faced by an English teacher in managing a large class and to describe strategies the teacher employed for that purpose.  It was conducted at a vocational school in Banyumas Regency, Central Java, Indonesia.  Descriptive qualitative approach was used in the study, with interview and observation as the main data collection techniques. One English teacher was involved as the research participant. Based on the interview with the English teacher, three difficulties arose when handling the large EFL classes: student grouping, use of English as language of instruction, and active student learning. Strategies the English teacher used in dealing with the large classes included: arranging seat position, grouping students, using appropriate media, controlling students, inserting humors, creating interactions, managing time, mentioning prohibition, telling stories, singing songs, and imposing punishment. In regard with strategies of handling EFL large size classes, the authors suggest a few other strategies for this purpose emerged from previous research experience. Key words: teacher strategies, large classroom, EFL, classroom management